Digital Literacy and Media Trust in Instagram-Based Da’wah Engagement: An Integrative Quantitative Model - Rahmawati, Endang; Rizky, Muhammad; Zukhrufillah, Irfani; Nasir, Badlihisham Bin Mohd (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
The rapid expansion of digital communication has intensified the circulation of religious content on social media, while simultaneously increasing exposure to misinformation. In this context, digital literacy and media trust are assumed to play a decisive role in shaping students’ engagement in digital da’wah. However, limited empirical research has examined the combined influence of these variables within an integrated framework. This study aims to analyze the partial and simultaneous effects of digital literacy and media trust on university students’ interest in conducting da’wah through Instagram. This research employed a quantitative correlational design. The sample comprised 75 students from the Islamic Communication and Broadcasting Study Program at IAIN Kendari and at Muhammadiyah Mataram University. Data were collected using a structured Likert-scale questionnaire and analyzed through multiple linear regression. The findings indicate that both digital literacy and media trust have positive, statistically significant effects on students’ interest in digital da’wah. Digital literacy emerged as the strongest predictor. Simultaneously, both variables explain 56% of the variance in students’ interest (R² = 0.560; p < 0.001), demonstrating substantial explanatory power. These results confirm that cognitive competence and affective trust jointly shape students’ participation in social media-based religious communication. This study contributes to the development of Islamic Broadcasting Communication by providing an integrative empirical model. Practically, it underscores the importance of strengthening digital literacy and fostering credible media environments to support responsible and active digital da’wah among university students.